2008
DOI: 10.1007/s11575-008-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Market Size, Legal Institutions, and International Diversification Strategies: Implications for the Performance of Multinational Firms

Abstract: and Key Results 0Recognizing that country-specifi c resources are generally diffi cult to imitate or diffuse across national boundaries, we propose that home country conditions are key determinants of fi rms' strategic choices. By embracing insights from both institutional economics and resource-based view, we identify two country-level environmental constituents -domestic market size and legal institutions -to examine how these resources infl uence multinational fi rms' international diversifi cation strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 91 publications
2
30
0
2
Order By: Relevance
“…≥500 emp. (e.g., Grant et al, 1988;Kang et al, 2011;Kistruck et al, 2013;Li & Yue, 2008;Qian, 2002;Tallman & Li, 1996). As indicated above, these results contradict the findings of studies conducted in less developed or emerging countries where the majority found a linear and positive relationship between PD and performance.…”
Section: Contributions To Scholarshipmentioning
confidence: 61%
“…≥500 emp. (e.g., Grant et al, 1988;Kang et al, 2011;Kistruck et al, 2013;Li & Yue, 2008;Qian, 2002;Tallman & Li, 1996). As indicated above, these results contradict the findings of studies conducted in less developed or emerging countries where the majority found a linear and positive relationship between PD and performance.…”
Section: Contributions To Scholarshipmentioning
confidence: 61%
“…Researchers following this approach have operationalized international diversification as the ratio of foreign sales to total sales (Capar and Kotabe 2003; Contractor et al . 2007; Elango and Sethi 2007; Gaur and Kumar 2009; Li and Yue 2008; Ruigrok and Wagner 2003; Ruigrok et al . 2007; Thomas 2006), the ratio of foreign assets to total assets (Daniels and Bracker 1989; Hsu and Pereira 2008; Mathur et al .…”
Section: International Experience and International Diversificationmentioning
confidence: 99%
“…Such difficulties will likely translate to poorer performance (Bloodgood, Sapienza, & Almeida, 1996). Firm size is usually measured using the logarithm of total sales (Belkaoui & Pavlik, 1992;Li & Yue, 2008) and/or the logarithm of total employees (Erramilli, 1996;Li, Zhou, & Shao, 2009). In this study, we used the logarithm of total sales of a firm to indicate firm size.…”
Section: Control Variablesmentioning
confidence: 99%